1991
DOI: 10.1021/la00053a007
|View full text |Cite
|
Sign up to set email alerts
|

Tensioactive properties of zwitterionic carboxybetaine amphiphiles

Abstract: Interfacial properties of zwitterionic surfactants having polymethylene intercharge arms of different length have been studied. Critical micelle concentration values, area per molecule, and surface tension values are all consistent with the following picture of the surfactant film: molecular interactions inside the interfacial film are electrostatic dipole-dipole and steric in origin. Steric interactions are predominant for large and flexible intercharge arm molecules for which the hydrophobic polymethylene ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
94
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 0 publications
15
94
0
Order By: Relevance
“…Furthermore, the formation of sodium chloride as the byproduct, which may tenaciously stick to the sulfobetaine moiety, required the purification of SHPP with a mixed bed ion exchanger, to obtain a monomer free of inorganic salt contamination. 28,29 Though reference data are missing, the 1 H-NMR spectra of SHPP (Fig. 2) fit well with the typical features of related sulfobetaine monomers.…”
Section: Resultssupporting
confidence: 57%
“…Furthermore, the formation of sodium chloride as the byproduct, which may tenaciously stick to the sulfobetaine moiety, required the purification of SHPP with a mixed bed ion exchanger, to obtain a monomer free of inorganic salt contamination. 28,29 Though reference data are missing, the 1 H-NMR spectra of SHPP (Fig. 2) fit well with the typical features of related sulfobetaine monomers.…”
Section: Resultssupporting
confidence: 57%
“…This problem has been remedied at least in parts by the use of ion exchange resins. Their use is particularly effective when inverting the second and third steps of the sequence shown in Scheme 6 [63,[86][87][88][89], so that the counterion X − in Im-2 becomes OH − and the final zwitterion is liberated without producing salts. However, this strategy cannot be applied universally due to the strongly alkaline conditions [86].…”
Section: Synthetic Strategies Towards Zwitterionic Moieties: Scope Anmentioning
confidence: 99%
“…This is particularly problematic at elevated temperatures or pH values. In fact, 3-ammoniopropionates have been described to be instable and to be in equilibrium with the ammonium acrylate salt that is formed after elimination [89,90,92]. This limits the usefulness of polyzwitterions bearing this motif severely, which has become rather popular these days due to their straightforward access.…”
Section: Synthetic Strategies Towards Zwitterionic Moieties: Scope Anmentioning
confidence: 99%
“…However, this trajectory is just a suggestion, as it is difficult to follow each peak unambiguously. (33,34,51)). Line broadening can be seen at intermediate detergent concentrations (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our study focuses on TRP3 accommodation at the hydrophilic/ hydrophobic interface of micelles and subsequent events. The structure and dynamics of TRP3 were examined in the presence of micelles of different chemical nature: zwitterionic (lysolauroylphosphatidylcholine 1-lauroyl-2-hydroxy-sn-glycero-3-phosphocholine (LLPC), n-dodecylphosphocholine (DPC), and N-dodecyl-N,N-(dimethylammonio) butyrate (DDMAB), anionic 1-myristoyl-2-hydroxy-sn-glycero-3-phospho-(1 0 -rac-glycerol) (LMPG), and nonionic (octylglucoside (OG)) (23,24,(31)(32)(33)(34)(35). The conformational ensemble was evaluated during detergent titration and it was found that the peptide interacts via conformational selection.…”
Section: Introductionmentioning
confidence: 99%